2015
DOI: 10.1103/physreve.92.032810
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic characterization of networks using graph polynomials

Abstract: In this paper, we present a method for characterizing the evolution of time-varying complex networks by adopting a thermodynamic representation of network structure computed from a polynomial (or algebraic) characterization of graph structure. Commencing from a representation of graph structure based on a characteristic polynomial computed from the normalized Laplacian matrix, we show how the polynomial is linked to the Boltzmann partition function of a network. This allows us to compute a number of thermodyna… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 34 publications
(72 citation statements)
references
References 40 publications
1
71
0
Order By: Relevance
“…Moreover, we would also like to further develop novel graph kernels through the dynamic time warping framework associated with other types of (hyper)graph characteristic sequences, e.g., the cycle numbers identified by the Ihara zeta function, the time-varying entropies computed from the continuoustime or discrete-time quantum walk [9,8], and the depth-based hypergraph complexity traces [3]. Finally, we are also interested in developing novel graph kernels for timevarying financial market networks [29], using the dynamic time warping framework.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we would also like to further develop novel graph kernels through the dynamic time warping framework associated with other types of (hyper)graph characteristic sequences, e.g., the cycle numbers identified by the Ihara zeta function, the time-varying entropies computed from the continuoustime or discrete-time quantum walk [9,8], and the depth-based hypergraph complexity traces [3]. Finally, we are also interested in developing novel graph kernels for timevarying financial market networks [29], using the dynamic time warping framework.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Ye et. al [3] present a novel method for characterizing the evolution of time-varying complex networks by adopting a thermodynamic representation of network structure computed from a polynomial (or algebraic) characterization of graph structure. This approach combines the theoretical tools developed for studying graph structure in the context of statistical mechanics of complex networks and clearly point the potentials of the current approach to study real-world time-varying networks.…”
Section: Introductionmentioning
confidence: 99%
“…The Maxwell-Boltzmann distribution relates the microscopic properties of particles to the macroscopic thermodynamic properties of matter [4]. It applies to systems consisting of a fixed number of weakly interacting distinguishable particles.…”
Section: Maxwell-boltzmann Statisticsmentioning
confidence: 99%
“…The properties of this physical heat bath system are described by a partition function with the energy microstates of the network represented by a suitably chosen Hamiltonian. Usually, the Hamiltonian is computed from the adjacency or Laplacian matrix of the network, but recently, Ye et al [4], have shown how the partition function can be computed from a characteristic matrix polynomial instead.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation